Effectiveness of treatments to prevent femoral periprosthetic bone loss following total hip arthroplasty: a network meta-analysis - Zhao, Zhi-Hu; Ling, Tao; Ye, Songqing; Luo, Wei; Ma, Jian-Xiong; Ma, Xinlong (Frontiers in Pharmacology, 2025)
BackgroundThe objective of this study was to conduct a systematic review and network meta-analysis (NMA) to compare the efficacy of various anti-osteoporosis drugs in preventing femoral periprosthetic bone loss following total hip arthroplasty (THA).MethodologyRandomized controlled trials (RCTs) assessing the clinical efficacy of various anti-osteoporosis drugs and control treatments in preventing periprosthetic bone loss following THA were identified. Outcomes evaluated included bone mineral density (BMD) at 6 months, 12 months, 24 months, and 5–10 years. The network meta-analysis was conducted using Stata 13.0 and R-3.5.1 software with the “gemtc” package.ResultsA total of 33 RCTs with 1,169 patients were included. At 6 months, alendronate, alendronate + alfacalcidol, denosumab, ibandronate, raloxifene, teriparatide + alendronate, and zoledronic acid were beneficial in increasing BMD, with denosumab ranking highest (based on surface under the cumulative ranking curve (SUCRA) values). At 12 months, alendronate, alendronate + alfacalcidol, denosumab, ibandronate, risedronate, and zoledronic acid showed benefits, with alendronate + alfacalcidol ranking highest (SUCRA = 0.97). For 24-month BMD, teriparatide + alendronate ranked highest (SUCRA = 0.82). Analysis of BMD at 5–10 years, involving four studies on alendronate, pamidronate, and placebo, indicated that alendronate achieved the highest SUCRA value (0.87).ConclusionBoth denosumab and bisphosphonates are effective in preventing femoral periprosthetic bone loss following THA. Denosumab was the most efficient agent for increasing BMD at 6 months post-THA, while alendronate combined with alfacalcidol or feriparatide was most efficient at 12 months and 24 months. More high-quality direct comparisons and long-term follow-up studies are needed to determine the optimal drug and dosage for THA patients.